Four new species of the genus Anillinus Casey (Coleoptera, Carabidae, Anillini) from Alabama, U.S.A., with a revised key to the Alabama species - Sokolov, Igor M. (Zootaxa, 2020)
Four new species of anilline ground beetles are described from Alabama. Two species from Jackson County, Anillinus clinei new species, and Anillinus folkertsioides new species, are troglobitic and litter species, respectively. Anillinus hildebrandti new species, is a troglobitic species from a cave in Morgan County. Anillinus humicolus new species, from Jefferson County is supposedly an endogean species. All new species are illustrated with images and drawings; a distribution map and a modified key to the Alabama species are provided. With these new discoveries, the known fauna of Anillinus of Alabama now includes twelve species. Species compositions of Anillinus based on habitat preferences of taxa satisfactorily explain the variations in total species numbers and number of endemics among Alabama and other eastern American states.